Association of Cross Linked C-Telopeptide II Collagen and Hyaluronic Acid with Knee Osteoarthritis Severity - John Butar Butar; Zola Wijayanti; Beatrix Tjahyana; Veli Sunggono; Hori Hariyanto (The Prodia Education and Research Institute (PERI), 2013)
BACKGROUND: This study was carried out to investigate the association of Cross Linked C-Telopeptide Type I & II Collagen (CTX-I and II) and hyaluronic acid (HA) with knee osteoarthritis (OA) severity.METHODS: Sixty menopause women with primary knee OA were enrolled in this study during their visits to the Outpatient Department. Patients with knee pain during weight bearing, active or passive range of motion, or tenderness with Kellgren-Lawrence (KL) grade of more than I were included. Patients with injury, inflammatory and metabolic diseases were excluded. Patients were put in a 10-hour fasting prior to withdrawal of morning blood samples for examinations of HA, CTX-I, interleukin 1 beta (IL-1β), and high sensitivity C reactive protein (hs-CRP) level. Second void morning urine specimens were taken for CTXII assessment. HA, CTX-I and II levels were measured by enzyme-linked immunosorbent assay.RESULTS: Sixty menopausal female patients were included in this study, 35 with KL grade II, 17 grade III, and 8 grade IV. Means of CTX-II were significantly different between subjects KL grade IV and III (p=0.021). Correlation of KL grade was significant with CTX-II (p=0.001, r=0.412) and HA (p=0.0411, r=0.269). KL grades were not significantly associated with CTX-I (p=0.8364, r=-0.0272); IL-1β (p=0.5773, r=0.0853) and hs-CRP (p=0.2625, r=0.1470).CONCLUSION: CTX-II and HA were associated with severity of knee OA, suggesting that CTX-II and HA can be used as marker for knee OA severity.KEYWORDS: CTX-II, hyaluronic acid, otestoarthritis, knee